Lack of clinical impact of 18F‐fluorodeoxyglucose positron emission tomography with simultaneous computed tomography for stage I and II Merkel cell carcinoma with concurrent sentinel lymph node biopsy staging: A single institutional experience from Westmead Hospital, Sydney. (13th October 2015) - Liu, Jui; Larcos, George; Howle, Julie; Veness, Michael
Abstract: Background/Objective: 18 F‐fluorodeoxyglucose (FDG) positron emission tomography with simultaneous computed tomography (PET‐CT) FDG PET‐CT plays an important clinical role in the staging and management of Merkel cell carcinoma (MCC) although its role in stage I and II disease relative to a sentinel lymph node biopsy (SLNB) is undefined. This study aimed to compare the clinical impact of FDG PET‐CT and SLNB on management in stage I and II MCC. Methods: This was a retrospective observational study. Between 2000 and 2014, 65 patients with biopsy‐proven MCC (all stages) underwent a staging FDG PET‐CT as part of their investigations in Westmead Hospital, Sydney. Since 2006, 26 patients have had an SLNB and of these, 16 underwent both an SLNB and FDGPET‐CT. All 16 patients had a histological diagnosis consistent with MCC without clinical evidence of regional or distant metastases prior to SLNB and FDG PET‐CT (stages IB and IIB). These patients were assessed with respect to MCC staging and the subsequent change of patient management post‐SLNB and FDG PET‐CT. Results: The SLNB identified occult lymph node metastases in 10 patients (63%), with FDG PET‐CT positive in only one patient (6%). Of the six SLNB‐negative patients, none demonstrated additional metastases on the FDG PET‐CT. Conclusions: In patients with stage I and II MCC, FDG PET‐CT is less sensitive than an SLNB in detecting occult metastatic lymph nodes. The routine use of FDG PET‐CT in these patients may not be justified.